2018
DOI: 10.5430/ijh.v4n2p20
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of mothers and caregivers on feeding practices of children under the age of five years with undernutrition in Oshikoto region, Namibia

Abstract: Background: Undernutrition in children under the age of five years is prevalent in the developing countries which increase the risk of morbidity and mortality among such age group. Lack of information related to nutrition and feeding practices as well as other factors such as employment and pressure from family and community members cause mothers and caregivers of children under the age of five years to use inappropriate methods of feeding which contribute to undernutrition. Purpose: The aim of this article is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…21 In a Namibian study entitled "Factors contributing to the development of undernutrition in children under the age of 5 years in Oshikoto Region" concluded that poor feeding practices, household food insecurity, and financial difficulties have greatly impacted the nutritional status of children under the age of 5 years. 22 A study conducted in Zambia highlighted the important aspects concerning risk factors that are associated with severe malnutrition in children with disabilities in low middle income countries (LMIC). It is reported that the risk factors for severe malnutrition among children with Cerebral Palsy are more related to the severity of the condition and caring practices.…”
Section: Current Knowledge On Malnutrition In Children Under Five Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In a Namibian study entitled "Factors contributing to the development of undernutrition in children under the age of 5 years in Oshikoto Region" concluded that poor feeding practices, household food insecurity, and financial difficulties have greatly impacted the nutritional status of children under the age of 5 years. 22 A study conducted in Zambia highlighted the important aspects concerning risk factors that are associated with severe malnutrition in children with disabilities in low middle income countries (LMIC). It is reported that the risk factors for severe malnutrition among children with Cerebral Palsy are more related to the severity of the condition and caring practices.…”
Section: Current Knowledge On Malnutrition In Children Under Five Yearsmentioning
confidence: 99%
“…34 Sanitation and hygiene practices can make significant differences in halting the cycle of infectious diseases and undernutrition. 22 It is however observed that sanitation in relation to malnutrition is under researched.…”
Section: Current Knowledge On Malnutrition In Children Under Five Yearsmentioning
confidence: 99%
“…Most of the studies that were done on mothers’ knowledge in terms of nutrition assessed the factors associated with malnutrition among children under the age of five years old, 14 and factors associated with undernutrition in the same study population. 7 Although studies have been done in Namibia on the knowledge and practices of mothers on nutrition, these only covered the Oshikoto region, 15 while Ashipala et al and Nangolo concentrated on exclusive breastfeeding in the northern east and Khomas regions respectively. 11 , 16 One of these studies revealed that the majority of mothers with malnourished children were uneducated and thus they had no knowledge of how to take care of their children.…”
Section: Introductionmentioning
confidence: 99%
“…Women on the frontlines are immensely proud [7]. However, women empowerment issues are still lack in government strategies to control COVID-19 and improve family well-being [8].…”
Section: Introductionmentioning
confidence: 99%